Exploring The Factors Lead To Commercial Building’s Operation And Maintenance Problems In Klang Valley - Tan, Yi Wang (2021)
This study aims to investigate the factors that lead to commercial building’s operation and maintenance problems in Klang Valley; understand better from the distinct perception of the parties involved in the building maintenance field. Furthermore, it aims to raise the awareness of building maintenance practitioners towards the operation and maintenance (O&M) practices; and explores the underlying factors impacting team effectiveness to improve operation and maintenance performance. A literature review on the O&M problems and the factors leading to commercial building O&M problems in Klang Valley. A total number of hundred (100) questionnaires were collected from the experts and individuals involved in commercial building works, such as Maintenance Technician, Facilities Operation Executive/ Manager, Building Manager, Building Technician, and others. The data obtained were analyzed statistically with several tests and entered into a computerized system known as SPSS software for data interpretation. The result got reconstructed, abstracted, and tabulated for further explanations. From the O&M problems in commercial buildings, water leakage problems ranked first from the RII results. Based on the five (5) main factors found, all five factor’s hypotheses are accepted and significantly impact commercial buildings’ O&M problems in Klang Valley. This paper furnishes a better understanding of the importance of O&M on commercial buildings and provides insights and raises awareness concerning the importance of commercial buildings’ O&M problems to a minimum level.